A Qur’anic Methodology for Integrating Knowledge and Education - Sidek Bin Baba (International Institute of Islamic Thought, 2015)
Integrating knowledge and education has become a major issue in Malaysia in the context of globalization. This study develops a teacher-centered Qur’anic methodology based on the integration of acquired (‘aqlī) and revealed (naqlī) knowledge as regards content, as well as the integration of teachers’ role in a teaching-learning process designed to empower students to manage “self” and “system.” It further investigates the existing curriculum and institutional efforts to integrate these two types of knowledge, students’ understanding of the integrated knowledge and its learning process, as well as how the teachers and lecturers understand this integrated knowledge and apply it to their teaching methods. Data collected through interviews and surveys of participating school students and teachers, as well as university students and lecturers, revealed several issues that need to be addressed.